Annotated record of the manganese nodules recovered from the Blake Plateau by Deepsea Ventures Inc. - James E Mielke (PANGAEA, 1976)
Analysis of manganese nodules recovered from the Blake Plateau by Deepsea Ventures Inc.
Supplement to: Mielke, JE (1976): Ocean manganese nodules. 94th U.S. Congress, 2nd Session, 2nd Edition. U.S. Government Printing Office, Washington; http://www.archive.org/details/oceaeseno00libr, 163 pp, https://store.pangaea.de/Projects/NOAA-MMS/mielke_1976.pdf